Let f(3) = 1, g(2) = 3, f'(3) = 4, g'(2) = 5. If h(x) = f(g(x)), ﬁnd h'(2). My professor got 20 for this. Why would you ignore g(2)? Wouldn't it be 4*3 * 5? Because the chain rule is f'(g(x)) * g'(x)
Follow Math Help Forum on Facebook and Google+
Originally Posted by habibixox Let f(3) = 1, g(2) = 3, f'(3) = 4, g'(2) = 5. If h(x) = f(g(x)), ﬁnd h'(2). My professor got 20 for this. Why would you ignore g(2)? Wouldn't it be 4*3 * 5? Because the chain rule is f'(g(x)) * g'(x) note that is substituted into the term ...
View Tag Cloud